Pentingnya Edukasi Cyber Security Untuk Menjaga Keamanan Data Pribadi dari Serangan Cyber Phishing Bagi Siswa/Siswi PKBM INTAN Tangerang Selatan - Akrom; Fingki Marwati; Aniq Astofa (CV. Multi Kreasi Media, 2024)
The rise of Cyber ​​attacks on the Internet is increasingly worrying and causing more and more victims, because the public needs to be educated about the importance of Cyber ​​Security and the importance of maintaining the security of personal data, especially for PKBM INTAN students and the general public. It cannot be denied that today's increasingly rapid technological progress can open up various new opportunities in good things, but also bad things, the ease of accessing the internet for everyone is one of the positive things, meaning that the effects of technological progress can be felt by everyone. almost all people, but this can become a problem and develop as a bad thing if people do not understand the threat of cyber attacks or criminal attacks via the internet, one of the cyber attacks that is increasingly worrying at the moment is cyber attacks via Phishing. One of the impacts or effects of a Phishing attack is that it can cause leakage of our personal data. Seeing the problems faced by the general public and INTAN PKBM Students in particular, we of time Lecturer PKM Universitas would like to provide outreach to INTAN PKBM Students with the title: